Currently recommended BK virus (BKV) plasma viral load cutoff of ≥4 log10/mL underestimates the diagnosis of BKV‐associated nephropathy: a single transplant center experience. Issue 1 (12th November 2013) - Hassan, S.; Mittal, C.; Amer, S.; Khalid, F.; Patel, A.; Delbusto, R.; Samuel, L.; Alangaden, G.; Ramesh, M.
Abstract Background BK virus (BKV)‐associated nephropathy (BKVAN) is a major cause of renal dysfunction and graft loss in renal transplant recipients. Monitoring plasma BK viral load (BKVL) is the recommended screening tool to predict BKVAN. American Society of Transplantation (AST) guidelines define a BKVL of ≥4 log10/mL (10, 000 copies) as presumptive BKVAN and recommend reduction in immunosuppression. We evaluated the clinical sensitivity of the quantitative BKV DNA assay in predicting risk for BKVAN using the AST‐recommended BKVL cutoff. Methods In a retrospective, single‐center study, all patients who underwent renal transplant at Henry Ford Hospital from January 2008 to August 2011 were analyzed (n = 490). Plasma BKVL Assay A (commercial large T antigen‐based polymerase chain reaction [PCR]) was done in all patients. Renal biopsy was done if there was a rise in serum creatinine ≥0.5 mg from baseline. BKVAN was confirmed by biopsy. As a subset to this study, from the same cohort, data for a set of 20 consecutive Assays A and B (in‐house VP1‐based PCR assay) from 15 patients over a period of 3 months were collected. Differences in physicians' clinical decision‐making (CDM) were analyzed between the 2 assays using chi‐square test. Results A total of 413 patients met the inclusion criteria, of which 222 patients had BK viremia. Among the 248 patients who had a renal biopsy done, 31 (12.5%) were found to have BKVAN. Eleven of the 31 (35%) patients had BKVL consistently <4 log10/mL, and thus were not diagnosed to have BKVAN using the AST‐recommended BKVL cutoff of ≥4 log10/mL. A total of 8 patients lost their graft owing to BKVAN, including 3 patients with BKVL <4 log10/mL. Using a cutoff point of plasma BKVL of ≥4 log10/mL, the sensitivity, specificity, positive predictive value, and negative predicative value of the PCR Assay A for the diagnosis of biopsy‐proven BKVAN were 64.5%, 98.4%, 87.0%, and 94.5%, respectively, and for the diagnosis of presumptive nephropathy were found to be 76.6%, 99.4%, 95.8%, and 96.4%, respectively. In the second part of the study, presumptive nephropathy was detected in 8 samples using Assay A and 14 samples using Assay B. Six samples in Assay A would have led to no changes in the CDM in terms of reduction in immunosuppression. Kidney biopsy was carried out in 5 patients, 4 of whom had BKVAN and had Assay B log count of ≥5. If Assay A had been used in CDM, BKVAN would have been missed in 1 patient. Conclusion Utilizing the current AST guideline cutoff of ≥4 log10/mL, the PCR Assay A underestimated the diagnosis of BKVAN. Urgent standardization of the various BKVL assays and establishment of universal cutoff points is imperative to avoid BKVAN‐related graft loss.